Verbal autopsy of neonatal deaths in Khatauli Block of District Muzaffarnagar, Uttar Pradesh, India - Muzammil, K; Singh, JV; Shankar, R (Nepal Journal of Epidemiology, 2014)
Background Verbal autopsy is a method of inquiry to ascertain the likely cause of death in populations where vital registration of deaths is incomplete and unreliable. Over 75% of deaths in India occur at homes; more than half of these do not have a certified cause. Further, most of the deaths in the rural areas of India occur at home and that is why a medical certification by a qualified practitioner is not possible. Keeping these facts in mind, this study was designed having objectives as to find out the causes of neonatal deaths through verbal autopsy and its feasibility to be used by health workers. Material & Methods: This cross-sectional epidemiological study was conducted in randomly selected rural areas of Khatauli Block of District Muzaffarnagar, Uttar Pradesh, India. Verbal autopsy data was collected by a team of health workers adequately trained for the same well in advance. Data related to reported neonatal deaths in the study area in the specified period of time was collected on structured & pre-tested questionnaire used as study tool by interviewing the parents, relatives or neighbours of the deceased. Data thus collected was verified twice by the coordinator and principal investigator respectively and analyzed by using Epi info statistical package. Results: A total of 24 perinatal deaths were reported, out of which 7 (29.2%) were stillbirth and 17 (70.8%) were neonatal deaths. ANC was received by 14 mothers (58.3%). Half of the deliveries were conducted by untrained Dai. About 20 deliveries (83.3%) were at home and 10 (58.8%) of the deceased were early neonates. The cause of deaths found by means of verbal autopsies were mainly: pneumonia - 4 (23.5%), diarrhoea - 2 (11.8%) neonatal jaundice - 03 (17.6%) etc. Conclusion: Pneumonia, diarrhoea & neonatal jaundice alone constitute about 53% of the total neonatal deaths. The use of the verbal autopsy tool by health workers to find out the cause of neonatal deaths is very much feasible. DOI: http://dx.doi.org/10.3126/nje.v4i5.12019 Nepal Journal of Epidemiology 2014; 4(5):423-27